2022
DOI: 10.1111/bjet.13275
|View full text |Cite
|
Sign up to set email alerts
|

Assessing approaches to learning with nonparametric multidimensional scaling

Abstract: This article reports on a trace‐based assessment of approaches to learning used by middle school aged children who interacted with NASA Mars Mission science, technology, engineering and mathematics (STEM) games in Whyville , an online game environment with 8 million registered young learners. The learning objectives of two games included awareness and knowledge of NASA missions, developing knowledge and skills of measurement and scaling, applying measurement for planetary comparisons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…With LDR, we assume that the subspace that best fits X is linear. LDR has been used in several healthcare applications because it is highly adaptable and effective in extracting features from large high dimensional datasets [ 27 , 28 , 29 ]. An example of LDR is multidimensional scaling (MDS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With LDR, we assume that the subspace that best fits X is linear. LDR has been used in several healthcare applications because it is highly adaptable and effective in extracting features from large high dimensional datasets [ 27 , 28 , 29 ]. An example of LDR is multidimensional scaling (MDS).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Knezek et al [ 27 ] used DR to assess various learning approaches to improve motivation amongst young learners. These authors applied MDS to add meaning and understanding to educational game play, and its effect on children’s learning performance.…”
Section: Methodsmentioning
confidence: 99%
“…Bernard et al (2022) 23 explored the impact of climate change on agricultural productivity in Africa using non-parametric analysis methods, which provided important insights for policy-making. In addition, Knezek et al (2023) 24 used non-parametric multidimensional scaling analysis to study students’ learning approaches and identified similarities and differences in learning styles across disciplines, which can inform educational quality evaluation. Overall, non-parametric analysis methods are indispensable tools for modern data analysis, and further development and refinement of these methods are necessary to better address practical challenges in different fields.…”
Section: Related Workmentioning
confidence: 99%
“…Park et al (2022) examined self‐regulatory learning behaviours of students studying with the adaptive learning analytics dashboard and identified groups of students relative to their learning strategies. Knezek et al (2022) utilised student trace‐data to unobtrusively assess learning behaviours of students studying in a game‐based learning environment. The authors identified several learning actions (eg, guess and page view ) and related those actions to course content to understand different learning approaches of individual students.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%